Smoking, Sex, and Non–Small Cell Lung Cancer: Steroid Hormone Receptors in Tumor Tissue (S0424). (13th January 2018) - Cheng, Ting-Yuan David; Darke, Amy K; Redman, Mary W; Zirpoli, Gary R; Davis, Warren; Payne Ondracek, Rochelle; Bshara, Wiam; Omilian, Angela R; Kratzke, Robert; Reid, Mary E; Molina, Julian R; Kolesar, Jill M; et al.
Abstract: Background: To what extent steroid hormones contribute to lung cancer in male and female never smokers and smokers is unclear. We examined expression of hormone receptors in lung tumors by sex and smoking. Methods: Patients with primary non–small cell lung cancer were recruited into an Intergroup study in the United States and Canada, led by SWOG (S0424). Tumors from 813 cases (450 women and 363 men) were assayed using immunohistochemistry for estrogen receptor (ER)–α, ER-β, progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2). Linear regression was used to examine differences in expression by sex and smoking status. Cox proportional hazard models were used to estimate survival associated with the receptors. All statistical tests were two-sided. Results: In ever smokers, postmenopause and oral contraceptive use were associated with lower nuclear ER-β ( P = .02) and total (nuclear + cytoplasmic) PR expression ( P = .02), respectively. Women had lower cytoplasmic ER-α (regression coefficient [β], or differences in H-scores = –15.8, P = .003) and nuclear ER-β (β = –12.8, P = .04) expression than men, adjusting for age, race, and smoking. Ever smokers had both higher cytoplasmic ER-α (β = 45.0, P < .001) and ER-β (β = 25.9, P < .001) but lower total PR (β = –42.1, P < .001) than never smokers. Higher cytoplasmic ER-α and ER-β were associated with worse survival (hazard ratio = 1.73, 95% confidence interval [CI] = 1.15 to 2.58, and HR = 1.59, 95% CI = 1.08 to 2.33, respectively; quartiles 4 vs 1). Conclusions: Lower expression of nuclear ER-β in women supports the estrogen hypothesis in lung cancer etiology. Increasing cytoplasmic ER-α and ER-β and decreasing PR protein expression may be mechanisms whereby smoking disrupts hormone pathways.